Linear Precoding for Multiuser Visible-Light Communication With Field-of-View Diversity - Renhai Feng; Mingjun Dai; Hui Wang; Bin Chen; Xiaohui Lin (IEEE Photonics Journal, 2016)
The multiple-input–multiple-output (MIMO) indoor visible-light communication (VLC) system with multiple users, where several light-emitting diodes (LEDs) send messages to several photodiodes (PD), is studied. To enhance the diversity, each user is assumed to be equipped with multiple PDs with a different field of view. The objective is to minimize the LEDs' maximum power consumption subject to multiple constraints, including illumination constraint and capacity constraint. Under the assumption of maximum-ratio combining at the receivers, a linear precoding method is proposed. Detailed operation of this precoding method includes two steps: First, with matrix transformation and semi-definite relaxation, the original nonconvex optimization problem is transformed into solvable convex optimization subproblems. Afterward, based on the solution of the subproblems, it is proved that a linear precoding solution can be reformulated using a rank-1 decomposition theorem. Numerical results show that our proposed scheme with different system parameters outperforms the traditional method.